Ending remedial programs? What your faculty can do. - JACQUELINE KRESS (Academic Chairpersons Conference Proceedings, 2019)
Remedial programs have not improved graduation rates and are being dropped across the US. What’s next? What can faculty do to support students’ learning? This session overviews current issues in remediation, provides opportunities to share chairs’ experiences, and introduces a strategy set faculty can use to support diverse learners.
Keywords: Remediation; student support; co-requisites; curriculum development; instructional strategies; higher education policy